Strengthening Emotional Literacy Through Children's Literature in Adaptive Learning: A Study of the Character Dru in the Novel Dru dan Kisah Lima Kerajaan by Clara Ng - Asysyifa, Fatma Nur; Lestari, Erawati Dwi (Faculty of Tarbiyah, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2025)
Strengthening emotional literacy is an important aspect of 21st-century education, emphasizing the development of students' social and personal intelligence. This article aims to examine how children's literature, specifically Clara Ng novel Dru dan Kisah Lima Kerajaan, can be used as an adaptive learning medium to foster the ability to understand, manage, and express emotions in a healthy manner. Through a literature review approach and literary psychology analysis, this article focuses on the main character, Dru, who experiences developments in emotional control throughout the story. The findings indicate that Dru's emotional experiences in dealing with conflict, pressure, and socio-cultural differences in the five kingdoms can reflect emotional dynamics that are familiar to children and adolescents. The character of Dru can be used as an adaptive learning resource, as it allows students to identify the character's emotions, evaluate their responses, and reflect on them in a real-life context on a personal level. Thus, children's literature not only has aesthetic and moral value but also plays an important role in building students' emotional literacy through flexible and contextual learning.